Epidemiology of adrenal tumours in Olmsted County, Minnesota, USA: a population-based cohort study. Issue 11 (November 2020) - Ebbehoj, Andreas; Li, Dingfeng; Kaur, Ravinder J; Zhang, Catherine; Singh, Sumitabh; Li, Taoran; Atkinson, Elizabeth; Achenbach, Sara; Khosla, Sundeep; Arlt, Wiebke; Young, William F; Rocca, Walter A; et al.
Summary: Background: Adrenal tumours are commonly encountered in clinical practice, but epidemiological data mainly originate from referral centres. We aimed to determine incidence, prevalence, and rates of malignancy and hormone excess in patients with adrenal tumours in a standardised geographically well defined population. Methods: In this retrospective population-based cohort study we assessed the standardised incidence rate of adrenal tumours in all patients with tumours who lived in Olmsted County, MN, USA, from Jan 1, 1995, to Dec 31, 2017. The Rochester Epidemiology Project infrastructure, which links medical records across all health-care providers for the entire population of Olmsted County since 1966, was used to allow researchers to identify individuals with specific diagnoses, surgical interventions, and other procedures, and to locate their medical records, which were then used in the analysis. Incidence rates and prevalence were standardised for age and sex according to the 2010 US Population. Findings: An adrenal tumour was diagnosed in 1287 patients (median age 62 years; 713 (55·4%) were women; and 13 (1·0%) were children). Standardised incidence rates increased from 4·4 (95% CI 0·3–8·6) per 100 000 person-years in 1995 to 47·8 (36·9–58·7) in 2017, mainly because of the incidental discovery of adenomas less than 40 mm in diameter in patients older than 40 years. Prevalence of adrenal tumours in 2017 was 532 per 100 000 inhabitants, ranging from 13 per 100 000 in children (aged <18 years) to 1900 per 100 000 in patients older than 65 years. 111 (8·6%) of 1287 patients were diagnosed with malignancy (96 [7·5%] of whom has metastases), 14 (1·1%) with phaeochromocytoma, and 53 (4·1%) with overt steroid hormone excess. Malignancy was more common in children (62%) versus those older than 18 years (8%; p<0·0001), tumours discovered during cancer-staging or follow-up (43% vs 3% for incidentalomas; p<0·0001), tumours more than 40 mm in diameter (34% vs 6% for tumours <20 mm; p<0·0001), tumours with unenhanced CT attenuation of 30 Hounsfield units or more (20% vs 1% for <20 Hounsfield units; p<·0001), and bilateral masses (16% vs 7% for unilateral, p=0·0004). Interpretation: Adrenal tumour standardised incidence rates increased 10 times from 1995 to 2017. Population-based data revealed lower rates of malignancy, phaeochromocytoma, and overt steroid hormone excess than previously reported. Funding: National Institutes of Health.